Approaches and challenges to the study of loess—Introduction to the LoessFest Special Issue. Issue 3 (11th May 2018) - Schaetzl, Randall J.; Bettis, E. Arthur; Crouvi, Onn; Fitzsimmons, Kathryn E.; Grimley, David A.; Hambach, Ulrich; Lehmkuhl, Frank; Marković, Slobodan B.; Mason, Joseph A.; Owczarek, Piotr; Roberts, Helen M.; Rousseau, Denis-Didier; et al.
Abstract: In September 2016, the annual meeting of the International Union for Quaternary Research's Loess and Pedostratigraphy Focus Group, traditionally referred to as a LoessFest, met in Eau Claire, Wisconsin, USA. The 2016 LoessFest focused on "thin" loess deposits and loess transportation surfaces. This LoessFest included 75 registered participants from 10 countries. Almost half of the participants were from outside the United States, and 18 of the participants were students. This review is the introduction to the special issue for Quaternary Research that originated from presentations and discussions at the 2016 LoessFest. This introduction highlights current understanding and ongoing work on loess in various regions of the world and provides brief summaries of some of the current approaches/strategies used to study loess deposits.